Pemberdayaan Literasi Digital untuk Pengembangan UMKM Kota Soe Kabupaten TTS - Suryaputra, Filipus Argentano Guntur; Demu, Yohanes; Arthana, I Komang (Penerbit Goodwood, 2024)
Purpose: This PKM has goals and solutions: (1) Helping to increase sales, (2) Expanding market share, (3) Outputs in this activity. Methodology: This activity began by socializing about the importance of this PKM activity which has good prospects for improving and progressing the business of MSME Actors in Soe City, South Central Timor Regency. This PKM Service Methods in the form of lecture and discussion methods. The activity was carried out in a Hybrid manner (Combined Offline and Online) with Zoom Pro. Results: In this PKM, the first speaker delivered a presentation on the characteristic profile of MSMEs in Soe and also detailed problems related to geographical conditions and awareness of MSME data collection administration. The second speaker conveyed the importance of digital literacy. The efforts of the service team in organizing the event have been successful due to the large number of MSME actors and government employees who have attended. Conclusions: The community service program aimed at enhancing digital literacy for Micro, Small, and Medium Enterprises (MSMEs) in Soe City, TTS Regency, successfully achieved its goal of providing the necessary digital understanding and skills for business development. These included: 1) Digital Marketing; 2) Digital Marketing Strategies; 3) Advantages of Digital Marketing; 4) Types of Digital Marketing; 5) Objectives of Digital Marketing; 6) Digital Marketing Trends; 7) SWOT Analysis of MSMEs in the Digital Era. Limitations: The limitations of this PKM include detailed aspects of assisting all MSMEs so that they are still registered on digital platforms are still very limited. Contribution: This contribution of service includes all representatives of MSMEs in Soe City, TTS Regency are able to market regional superior products so that they can compete with larger companies by upholding local aspects.